Geomagnetic Energy Approach to Space Debris Deorbiting in a Low Earth Orbit - Guanhua Feng; Wenhao Li; Heng Zhang (International Journal of Aerospace Engineering)
The space debris removal problem needs to be solved urgently. Over 70% of debris is distributed between the 500 km and 1000 km low Earth orbits (LEO), and existing methods may be theoretically feasible but are not the high-efficiency and low-consumption methods for LEO debris removal. Based on the torque effect of a static magnet interacting with the geomagnetic field, a new spin angular momentum exchange (SAME) method by geomagnetic excitation (without working medium consumption) for LEO active debris deorbiting is proposed. The LEO delivery capability of this method is researched. Two kinds of spin angular momentum accumulation (SAMA) strategies are proposed. Then through numerical simulation under the dipole model and International Geomagnetic Reference Field (IGRF11) model, the results confirm the physical feasibility and basic performance of the proposed method. The method can be applied to the regions of the LEO below 1000 km with different altitudes/inclinations and eccentricities, and with existent magnetorquer technology, only several days of preparation is required for about 104 m·kg mechanism-scale-debris-mass deorbiting, which can be used for deorbiting missions in debris-intensive areas (altitude≤1000 km); without consideration of external effects on the geomagnetic field distribution, it has the same deorbiting capability with that of the LEO below 1000 km when the altitude is over 1000 km. Besides, the method is characterized by explicit mechanism, flexible control strategy and application, and low dependence on the scale. Finally, the key technology requirements and future application of LEO active debris removal and on-orbit delivery by using SAME are prospected.